2022
DOI: 10.3390/v14102182
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Upper Respiratory Tract Transcriptomic Profiling Reveals a Potential Role of Early Activation of Interferon Pathway in Severe COVID-19

Abstract: Infection with SARS-CoV-2 results in Coronavirus disease 2019 (COVID-19) is known to cause mild to acute respiratory infection and sometimes progress towards respiratory failure and death. The mechanisms driving the progression of the disease and accumulation of high viral load in the lungs without initial symptoms remain elusive. In this study, we evaluated the upper respiratory tract host transcriptional response in COVID-19 patients with mild to severe symptoms and compared it with the control COVID-19 nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The univariate analysis also found that IFN-β expression levels increased with increasing pneumonia severity. Since IFN-β induces the expression of ISGs [18 , 19] , the low expression of RIG-I, ISG15, CCL5 , and CXCL10 seems contradictory. However, Sposito et al .…”
Section: Discussionmentioning
confidence: 99%
“…The univariate analysis also found that IFN-β expression levels increased with increasing pneumonia severity. Since IFN-β induces the expression of ISGs [18 , 19] , the low expression of RIG-I, ISG15, CCL5 , and CXCL10 seems contradictory. However, Sposito et al .…”
Section: Discussionmentioning
confidence: 99%
“…(iv) Heightened interferon response. SARS-Cov-2 infection causes a massive elevation in the expression of interferon-stimulated genes, as measured in leukocytes and in material from invasive biopsies (35)(36)(37). The identification of an interferon response in cell-free chromatin underscores the potential of epigenetic liquid biopsies to reveal gene expression program in cells prior to their death.…”
Section: Tissue Dynamics In Covid-19mentioning
confidence: 99%